Comparison of the lung clearance index in preschool children with primary ciliary dyskinesia and cystic fibrosis - Röhmel, Jobst Fridolin; Dörfler, Friederike J.; Körner-Rettberg, Cordula; Brinkmann, Folke; Schlegtendal, Anne; Wetzke, Martin; Rudolf, Isa; Helms, Simone; Große-Onnebrink, Joerg; Yu, Yin; Nüßlein, Thomas Georg; Wojsyk-Banaszak, Irena; et al. (Chest, 2022)
Background - Previous studies showed that the lung clearance index (LCI) determined by multiple-breath washout (MBW) is sensitive to detecting early lung disease in preschool children with cystic fibrosis (CF). In preschool children with primary ciliary dyskinesia (PCD), data on the onset and severity of lung disease and on the sensitivity of the LCI as a noninvasive quantitative outcome measure remain limited. - Research and Study Question - Is MBW feasible and sensitive to detect ventilation inhomogeneity in preschool children with PCD? - Study Design and Methods - This was a prospective, cross-sectional, multicenter study and included preschoolers with PCD, preschoolers with CF, and healthy control (HC) participants. LCI was determined using nitrogen MBW and was compared among the three groups. - Results - LCI was determined in 27 children with PCD, 34 children with CF, and 30 HC participants (mean age, 4.8 years; range, 2.2-6.9 years). The LCI in preschool children with PCD was increased (median, 9.1; 95% CI, 8.6-10.3) compared with HC participants (median, 7.0; 95% CI, 6.7-7.1; P < .0001), but did not differ from preschool children with CF (median, 8.6; 95% CI, 8.4-9.7; P = .71). The feasibility in the PCD group was 93.1% and was similar to that in the CF group (91.9%) and in HC participants (85.7%; P = .55). - Interpretation - This study demonstrated early onset of lung disease in preschool children with PCD and indicated that lung disease severity in PCD may be similar to that in CF during preschool years. These data support a need for early diagnostic monitoring and therapy and suggest the LCI as a noninvasive diagnostic tool and as a potential end point in clinical trials testing early interventions in children with PCD.